1984
DOI: 10.1029/ja089ia02p00997
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of the ionopause of Venus

Abstract: We examine the stability of the of gravitation has not been considered before. In Venus ionopause in light of the importance of addition we intend to take into acco,•nt the gravitation and curvature. Using a one fluid effect of the curvature of the VenusJan ionoapproximation for the equation of motion of the pause. The centrifugal acceleration of the ionoplasma, and ignoring the effects of neutrals, we spheric plasma, g = V2/R (where V 2 is the sum of obtain a dispersion relation that includes the the squares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 22 publications
0
42
2
Order By: Relevance
“…The interface between the magnetosheath and ionospheric plasmas is also a site for possible fluid-like MHD instabilities (Wolff et al 1980;Dubinin et al 1980;Elphic and Ershkovich 1984;Thomas and Winske 1991;Arshukova et al 2004). The observations of the surface waves near the Venusian ionopause and detached clouds of ionospheric plasma in the magnetosheath ) confirm this suggestion.…”
Section: Boundary Layer/mantlementioning
confidence: 98%
“…The interface between the magnetosheath and ionospheric plasmas is also a site for possible fluid-like MHD instabilities (Wolff et al 1980;Dubinin et al 1980;Elphic and Ershkovich 1984;Thomas and Winske 1991;Arshukova et al 2004). The observations of the surface waves near the Venusian ionopause and detached clouds of ionospheric plasma in the magnetosheath ) confirm this suggestion.…”
Section: Boundary Layer/mantlementioning
confidence: 98%
“…Although few measurements are available at Mars, similar processes have been observed at Venus. There, thermal ion measurements made from Pioneer Venus revealed a complex morphology of the ionosphere upper boundary near the Venus terminator and in the wake, consisting of waves, streamers, and detached ionospheric "clouds" (Brace et al 1982), which might have been generated by Kelvin-Helmholtz (K-H) instability (Elphic and Ershkovich 1984) or by magnetic tension ("slingshot") related to the draped solarwind magnetic fields. At Mars, the presence of crustal magnetic fields interacting with shocked solar wind plasma makes possible additional bulk escape mechanisms, including magnetic reconnection (Eastwood et al 2008) and plasmoid-type structures (Brain et al 2010).…”
Section: Ion Bulk Escapementioning
confidence: 99%
“…This large separation in a direction perpendicular to the magnetosheath flow suggests that the ionospheric plasma in the clouds must have originated in the ionosphere upstream on the dayside, indicating that magnetohydrodynamic (MHD) instabilities may occur at the Venusian ionopause, which was first suggested by Wolff et al (1980). Elphic and Ershkovich (1984) analyzed the stability of the Venusian ionopause by using one-fluid MHD equations for a perfectly conducting, incompressible, inviscid fluid, and concluded that the Kelvin-Helmholtz instability is the dominant instability over most of the dayside ionopause. After that, the Venusian solar wind-ionosphere interaction was analyzed using analytical (e.g., Cloutier et al, 1983;Elphic and Ershkovich, 1984) and numerical models (e.g., Thomas and Winske, 1991).…”
Section: Introductionmentioning
confidence: 95%
“…Elphic and Ershkovich (1984) analyzed the stability of the Venusian ionopause by using one-fluid MHD equations for a perfectly conducting, incompressible, inviscid fluid, and concluded that the Kelvin-Helmholtz instability is the dominant instability over most of the dayside ionopause. After that, the Venusian solar wind-ionosphere interaction was analyzed using analytical (e.g., Cloutier et al, 1983;Elphic and Ershkovich, 1984) and numerical models (e.g., Thomas and Winske, 1991). Recently, Terada et al (2002) used a global hybrid simulation to describe the Kelvin-Helmholtz instability at Venus.…”
Section: Introductionmentioning
confidence: 99%